Exploring the Intersection between Databases and Digital Forensics - B. Seufitelli, Danilo; A. Brandão, Michele; Moro, Mirella M. (Journal of Information and Data Management, 2022)
Digital forensics has attracted attention from assorted researchers, who primarily work on predicting and solving digital hacks and crimes. In turn, the number and types of digital crimes have increased considerably, mainly due to the growing use of digital media to perform daily personal and professional tasks. Like most computer-related activities, data is at the center of such hacks and crimes. Hence, this work presents a systematic literature review of publications at the intersection between Digital Forensics and Databases. We discuss problems and trends of two main categories: Data Building and Database Management Systems. Overall, this research opens the doors for the communication between databases and an area with several exciting and concrete challenges, with great potential for social, economic, and technical-scientific contributions.